2012
DOI: 10.1158/1078-0432.ccr-11-2630
|View full text |Cite|
|
Sign up to set email alerts
|

Expansion of a CD8+PD-1+ Replicative Senescence Phenotype in Early Stage CLL Patients Is Associated with Inverted CD4:CD8 Ratios and Disease Progression

Abstract: Purpose: Patients with chronic lymphocytic leukemia (CLL) display immune deficiency that is most obvious in advanced stage disease. Here we investigated whether this immune dysfunction plays a pathologic role in the progression of early stage disease patients.Experimental Design: We carried out eight-color immunophenotyping analysis in a cohort of 110 untreated early stage CLL patients and 22 age-matched healthy donors and correlated our findings with clinical outcome data.Results: We found a significant reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
163
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(180 citation statements)
references
References 44 publications
16
163
0
1
Order By: Relevance
“…16,19,[22][23][24][25] The precise role that different T-cell subsets play in the immunodeficiency of CLL remains undetermined but functional studies have identified defects in immune synapse formation, costimulatory/accessory molecule expression and cytokine release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,19,[22][23][24][25] The precise role that different T-cell subsets play in the immunodeficiency of CLL remains undetermined but functional studies have identified defects in immune synapse formation, costimulatory/accessory molecule expression and cytokine release.…”
Section: Discussionmentioning
confidence: 99%
“…16,19,[22][23][24][25] The precise role that different T-cell subsets play in the immunodeficiency of CLL remains undetermined but functional studies have identified defects in immune synapse formation, costimulatory/accessory molecule expression and cytokine release. [15][16][17] Despite these problems, several T-cell-based therapeutic strategies have been tried in CLL including adoptive transfer of anti-CD3/anti-CD28 activated T cells, 26 T cells expressing chimeric antigen receptors, and vaccine therapy with dendritic cells pulsed with CLL-cell lysates.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell exhaustion has been proposed as an important mechanism involved in CLL pathogenesis, 5,6,8 leading to a general hyporesponsiveness of T cells in CLL. As such, the clones observed in our study may be functionally silent and not necessarily provide relevant T-cell help for CLL.…”
Section: A B C D E F Gmentioning
confidence: 99%
“…As recent reports suggested T-cell exhaustion, a functional silencing of T cells, to be involved in the development of CLL, [5][6][7] we also assessed the expression of the exhaustion marker programmed death-1 (PD-1) on over-represented T cells. Thereby Figure 2F and Online Supplementary Table S3), suggesting that clonal T cells are likely to be an exhausted T-cell fraction.…”
mentioning
confidence: 99%
“…The mechanisms that underlie the reduction in immune competence are multifactorial but include hypogammaglobulinemia and T cell dysfunction 13. In addition, the burden of chronic infection and changes in the T cell repertoire are also important for overall prognosis in B‐CLL, and an inverted CD4:CD8 T cell ratio is associated with disease progression 14. The CD4:CD8 ratio is markedly lower in CMV seropositive individuals compared with those who remain uninfected, and this effect is particularly profound in patients with CLL.…”
Section: Introductionmentioning
confidence: 99%